Introducing robotic process automation to your organization : a guide for business leaders - Fantina, Robert; Storozhuk, Andriy; Goyal, Kamal (Apress, 2022)
For your robotic process automation (RPA) program to be successful, you need to follow a general framework and governance model. This book covers, in detail, what they should look like and how to adapt them to your organization. Introducing Robotic Process Automation to Your Organization is structured to enable you, a novice to RPA, to successfully implement an RPA program at your company. RPA is rapidly growing in use, but is only starting to be taught at a university level. Many mid-level managers will be tasked with introducing an RPA program at their organizations as senior management learns of its efficacy, but will be unfamiliar with how to do so. This book provides you with the skills and information you need to make an informed decision. ​For decades, there has been much discussion about the fast pace of technology, the rapidly changing technology environment, and the need for companies to be on the cutting edge to remain competitive or even relevant. In this ever-changing environment, there is a need to know what can be done in terms of current processes, here and now, that will increase efficiency, benefit customers, and improve profitability. One option is RPA. This book includes information to assist you in getting the required buy-in and identifying the first few processes for automation. A structure for identifying opportunities on an ongoing basis is detailed, along with concepts that must be considered for solution design and deployment. Throughout the book there are several "pause and consider" statements to help you think about how principles pertain to your organization. Additionally, there are tips included that offer short, concrete suggestions on how to help implement the particular step being discussed. What You Will Learn Know the benefits of robotic process automation (RPA) Understand the limitations of RPA Ask the right questions to determine whether a process is a good candidate for automation Obtain buy-in from skeptics at the senior and middle manager levels, and from line workers Be familiar with the structure required for success Who This Book is For Middle managers who have either identified the need for robotic process automation (RPA) in their organization or have been directed by senior management to explore the possibility of introducing RPA to their organization; managers at all levels who hear about RPA, either through conferences, professional associations, or industry publications, and want to know more;...